Clozapine combined with different antipsychotic drugs for treatment resistant schizophrenia. - Cipriani, A; Boso, M; Barbui, C (2009)
BACKGROUND: Although clozapine has been shown to be the treatment of choice in people with schizophrenia that are resistant to treatment, one third to two thirds of people still have persistent positive symptoms despite clozapine monotherapy of adequate dosage and duration. The need to provide effective therapeutic interventions to patients who do not have an optimal response to clozapine is the most common reason for simultaneously prescribing a second antipsychotic drug in combination with clozapine. OBJECTIVES: To determine the efficacy and tolerability of various clozapine combination strategies with antipsychotics in people with treatment resistant schizophrenia. SEARCH STRATEGY: We searched the Cochrane Schizophrenia Group Trials Register (March 2008) and MEDLINE (up to November 2008). We checked reference lists of all identified randomised controlled trials and requested pharmaceutical companies marketing investigational products to provide relevant published and unpublished data. SELECTION CRITERIA: We included only randomised controlled trials recruiting people of both sexes, aged 18 years or more, with a diagnosis of treatment-resistant schizophrenia (or related disorders) and comparing clozapine plus another antipsychotic drug with clozapine plus a different antipsychotic drug. DATA COLLECTION AND ANALYSIS: Two review authors independently extracted data and resolved disagreement by discussion with third member of the team. When insufficient data were provided, we contacted the study authors. MAIN RESULTS: Three small (range of number of participants 28 to 60) randomised controlled trials were included in the review. Even though results from individual studies did not find that one combination strategy is better than the others, the methodological quality of included studies was too low to allow authors to use the collected data to answer the research question correctly. AUTHORS' CONCLUSIONS: In this review we considered the risk of bias too high because of the poor quality of the retrieved information (small sample size, heterogeneity of comparisons, flaws in the design, conduct and analysis). Although clinical guidelines recommend a second antipsychotic in addition to clozapine in partially responsive patients with schizophrenia, the present systematic review was not able to show if any particular combination strategy was superior to the others. New, properly conducted, randomised controlled trials independent from the pharmaceutical industry need to recruit many more patients to give a reliable estimate of effect or of no effect of antipsychotics as combination treatment with clozapine in patients who do not have an optimal response to clozapine monotherapy.